Metonymic uses of the concept “Heart” in Uzbek, English Russian - Madaminova Iroda (Zien Journals, 2022)
This article explains the metonymical meaning of the “Heart” concept in the literary texts and language system. Here given comparative analysis of the concept heart in three languages: English, Uzbek, and Russian. In the article, we looked through the similarities and difference of the “Heart” concept in three languages. The Heart concept is studied by a number of English and Russian scientists. However, there are fewer scientists who carry out research of concept “Heart” in Uzbek language. Here the concept “Heart” is analyzed in three languages.
Keywords: concept; conceptual meaning; metonymical meaning; Idiosyncratic English expressions